(untitled) (Revista de Investigaciones Universidad del Quindío, 2018)
This article represents a first approach to the zoning process of the suitability of materials for construction as a contribution to the identification of sources of quarry material in the Department of Quindío. In this project was determined particularly the aptitude of stone materials for road construction uses. The analysis was carried out based on compliance with the quality requirements demanded by current Colombian regulations, mainly the INVIAS standard. The information in which the analysis of aptitude of the stone materials is based was obtained from the SUB09-25 Project of INGEOMINAS (today Colombian Geological Service, SGC), associated to the Division of Industrial Minerals and Construction Materials, in which they were extracted rock samples from the mountainous area of Quindío and were subjected to laboratory tests for further characterization. As a final product it presents a SIG map with the zoning of the geological units in the Department of Quindío suitable for the exploitation of aggregates for the construction of roads.